Implementation of Mediation in Schools: Issues in Latvia - Truskovska, Ženija; Orska, Rita; Ušča, Svetlana (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
The article provides overview of issues related to the implementation of mediation in schools in Latvia, as well outlines the practical research carried out in Rezeknes Augstskola. This is another attempt to trigger the topic and to initiate the discussion in Latvia on mediation as a modern and alternative method for problem and conflict solution in schools, involving in the process both students and adults thus endorsing tolerance, empathy, and non-violent communication.